Pendampingan Pemasaran yang Terencana dan Pengembangan Desain Produk Untuk Meningkatkan Daya Saing UMKM Madu Sumbawa di Kabupaten Sumbawa - Edi Irawan; Hanifa Sri Nuryani; Fitriah Permata Cita; Didi Suwardi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
MSMEs play a vital role in Indonesia's economy, society, and culture. However, some MSMEs, such as "Madu Sumbawa" in Sumbawa Regency, still face challenges in marketing, packaging, and product labeling. Therefore, mentoring activities are conducted to improve the quality and competitiveness of these MSMEs. The approach implemented includes focus group discussions and interviews with MSME owners, as well as mentoring in marketing strategies, packaging, and product labeling. Results achieved include the establishment of a structured marketing system, both online and offline, the use of packaging with digital printing technology, and attractive product labeling that complies with applicable regulations. This mentoring aims to provide added value to MSMEs, so they can be more competitive in local and global markets with more attractive and standard-compliant products. In addition, with this mentoring, MSMEs can improve their ability to utilize digital media, expand market reach, and enhance product image, which will increase competitiveness in an increasingly competitive market.